International Council of Women records - International Council of Women
Correspondence, minutes of meetings, reports, press releases, and publications reflecting the council's role in cinematography, disarmament, education, peace, and other global issues. Includes material on two pioneer conferences on educational films held at the International Institute of Educational Cinematography of the League of Nations (1931, 1934); on the general, regional, and New York meetings of the Conference of International Non-governmental Organizations in coordination with the United Nations (1948-1954); and the Disarmament Committee of the Women's International Organisations, later the Peace and Disarmament Committee of the Women's International Organisations.
International Council of Women (ICW) founded in Washington, D.C., in 1888, as an international federation of national women's organizations. Later affiliated with the United Nations with headquarters in Paris.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Disarmament Committee of the Women's International Organisations; International Institute of Educational Cinematography; League of Nations; Peace and Disarmament Committee of the Women's International Organisations; United Nations; Cinematography; Disarmament; Education; Motion pictures in education -- Congresses; Peace; Women -- International cooperation